ECONOMIC EVALUATION OF PT XYZâS UNDERGROUND SUB-LEVEL STOPE MINE USING DISCOUNTED CASH FLOW AND REAL OPTION ANALYSIS METHOD - Fauzan Pulungan, Aqsal
The sub-level stoping gold mining method involves filling material into the stope that has been mined, making operating costs for mining even higher. The general approach to economic evaluation using the Discounted Cash Flow method is deemed insufficient to assess the economics, so other methods are needed that can consider uncertainty factors and can provide information on the magnitude of the opportunity for the project value. The Real Option Valuation (ROV) method using Binomial Lattice and Rainbow Option has management flexibility to overcome uncertainties that may occur. The evaluation begins with the DCF method which will produce Net Present Value and Internal Rate of Return. From the sensitivity analysis carried out on the parameters of commodity selling prices and operating costs, it will show changes in the economic value of PT XYZ's mine that occur if the parameters mentioned change. The economic evaluation will continue using the ROV method using Binomial Lattice and Rainbow Option to determine the economic value of the project. The DCF method produces a project NPV of IDR 974,722,524,327.78 with an IRR of 37.8%. Sensitivity analysis shows that selling price is the most sensitive parameter and operating costs are very dependent on inflation. Based on the Binomial Lattice approach for historical data for the last 6 years and 12 years, the project has an option premium on the commodity selling price parameter of IDR 105,282,837,167.87 and IDR 220,419,855,122.98, while based on the inflation parameter the option premium value is IDR 176. 146,333,615.87 and Rp. 197,293,476,530.02. The project also has an option premium based on the Raibow Option on historical data on selling prices and inflation for the last 12 years amounting to IDR 541,498,207,763.06 and historical data on selling prices and inflation for 6 years amounting to IDR 760,457,902,352.72.